MARKETING MIX DAN PERILAKU KONSUMEN KEDAI KOPI DI KECAMATAN MAJALAYA - Rendy Abdul Mughni; iwan Setiawan (Universitas Galuh, 2023)
The development of the world of coffee drinks has caused the demand for coffee to increase and coffee shops have begun to appear in various regions. The number of coffee shops that have sprung up has caused intense business competition in the coffee sector which requires coffee business people to develop their businesses in order to have more attractiveness to coffee consumers. This study aims to determine consumer characteristics, analyze the relationship between characteristics and consumer behavior, and analyze the impact of marketing mix on coffee shop consumer behavior. The sampling method is carried out by accidental sampling technique. The analysis methods used are descriptive analysis, Spearman Rank correlation, and Logistic Regression. The results showed that coffee shop consumers are dominated by consumers aged 18-27 years (youth), the last education / being pursued is a diploma / bachelor, income Rp.1,000,000 - Rp.3,000,000, have no dependents and the distance from home to the coffee shop is between 1-3 km. The characteristics of the age and income of the consumer, the level of education, the number of dependents, and the distance from home to the coffee shop are in real contact with consumer behavior. The product, place, and promotion components have a real effect on coffee consumer behavior but with a low influence, while the price component has no influence. Coffee attributes that must be maintained are the attributes of facilities, cleanliness, easy to reach, fragrance, menu variations, and advertising promotion.